Chemical control of Diaphorina citri Kuwayama (Hemiptera: Psyllidae) in Persian lime Citrus latifolia Tanaka - Hernández-Fuentes, Luis Martín; Urias-López, Mario Alfonso; López-Arroyo, José Isabel; Gómez-Jaimes, Rafael; Bautista-Martínez, Néstor (Revista Mexicana de Ciencias Agrícolas, 2018)
Citrus crops represent an outstanding activity at worldwide level. Mexico ranks fourth place in production. Due introduction and dispersion of D. citri vector in all citric zones from Mexico and the newly detected disease known as huanglongbing (HLB) caused by Candidatus Liberibacter asiaticus bacteria, assessment of control methods for this bug is required. In 2010, technical effectiveness in field and persistence for different action route against Persian lime D. citri chemical products tests were performed in Nayarit, Mexico. Two assessments were made at different dates. The amount of nymphs per shoot and percentage of infested shoots were assessed in each rehearsal. From evaluated products, dimethoate, imidacloprid and the mixture of imidacloprid and β-cyfluthrin exerted more than 85% percent of control against nymphs during 27 days after application. In trees treated with dimethoate and imidacloprid in 400 mL and 300 mL ha-1 dose, respectively, 100% of shoots free of D. citri nymphs at 27 days after application was observed. Agricultural oil in two and three L ha-1 dose exerted less control against D. citri nymphs.
Keywords: Diaphorina citri; chemical control; citric